Needs analysis for the development of an augmented reality-based learning module on isometric transformation for Malaysian form 2 students - Osman, Noorul Shuhadah; Mohd Ayub, Ahmad Fauzi; Zulkifli, Nurul Nadwa (Journal of Islamic, Social, Economics and Development, 2025)
Augmented reality (AR) has emerged as a promising educational technology, offering immersive and interactive learning experiences that enhance student engagement and support conceptual visualization. In the Malaysian Form 2 mathematics curriculum, isometric transformations which include translations, reflections, and rotations, are foundational yet conceptually challenging topics. Traditional instructional methods often fail to effectively assist students in visualizing and understanding these transformations, resulting in learning gaps and reduced motivation. The interactive nature of AR holds potential to address these issues by enabling real-time visualization of transformations, thereby improving students’ spatial reasoning, academic performance, and motivation to learn. This study aimed to conduct a comprehensive needs analysis to inform the development of an AR-based learning module focused on isometric transformations for Malaysian Form 2 students. A qualitative research approach was employed, involving structured interviews with five mathematics education experts from five different Malaysian states. Interview data were analyzed thematically, with transcripts coded and categorized into key themes. The findings revealed that isometric transformations, particularly those in the Form 2 syllabus, are essential for students’ mathematical development. Experts unanimously agreed that integrating AR technology into learning modules offers significant pedagogical value for teaching this topic. Furthermore, they emphasized that the module’s design should align with classroom teaching practices, including notes and activities. These insights provide a valuable foundation for developing an effective and contextually relevant AR-based instructional module.